THE ROLE OF FINANCIAL INITIATIVE ON FINANCIAL PERFORMANCE - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Financial initiative, government policy related to taxation and public spending. Fiscal policy and monetary policy, which is concerned with money supply, are the two most important components of a government’s overall economic policy, and governments use them in an attempt to maintain economic growth, high employment, and low inflation.J. Nogueira Martins (2009) Financial policy can be either expansionary or contractionary. It is expansionary or loose when taxation is reduced or public spending is increased with the aim of stimulating total spending in the economy, known as aggregate demand. Expansionary policy might occur when a government feels its economy is not growing fast enough or unemployment is too high. By increasing spending or cutting taxes, the government leaves individuals and businesses with more money to purchase goods or invest in new equipment. When individuals or firms increase their purchases, they raise demand, which requires additional production, creating jobs and generating more spending. The result is higher employment and a growing economy.